Distribution of MecA and Erm Genes among Methicillin-resistant Staphylococcus Aureus with Inducible Resistance to Clindamycin - Malla Thakuri, Dudha Raj; Pokhrel, Anil; Amatya, Ritu; Sharma Bashyal, Narayan; Neupane, Mary; KC, Sudeep; Joshi, Dev Raj; Khanal, Santosh (Journal of Nepal Health Research Council, 2023)
Background: The emergence of Methicillin-resistant Staphylococcus aureus and its ability to confer cross-resistance to macrolide-lincosamide-streptogramin B has complicated the treatment against it. Gene-based studies among phenotypic methicillin-resistant isolates with inducible resistance to clindamycin are less available in Nepal. This work was undertaken to detect the mecA and erm genes among such phenotypes isolated from clinical samples. Methods: S. aureus isolated from different clinical samples was identified by standard microbiological procedures (Gram-staining, colony morphology, and different biochemical tests). Methicillin-resistant and inducible resistant to clindamycin phenotypes were detected by using cefoxitin disc (30 µg) and a double disk diffusion test according to the Clinical and Laboratory Standards Institute guidelines and mecA and erm genes were detected by polymerase chain reaction.Results: Among 120 S. aureus isolates, 51.67% (n=62) were MRSA, and the prevalence of inducibly-resistant, constitutively-resistant and Macrolide-Streptogramin phenotypes were 15.83% (n=19), 28.33% (n=34) and 15.83% (n=19) respectively. While 35.84% (n=43) of isolates showed sensitivity to both antibiotics, erythromycin and clindamycin. Out of 14 inducibly-resistant phenotypes, 57.14% (n=8) were found carrying ermC and 28.57% (n=4) phenotypes contained both ermA and ermC. All phenotypes were positive for the mecA gene.Conclusions: Macrolides-Lincosamide-Streptogramin B resistance was predominant among methicillin-resistant S. aureus. While all isolates with inducible clindamycin resistance harbored mecA gene, most of them also harbored ermC gene. The higher prevalence of inducible-resistant to clindamycin indicated the need for rational use of antimicrobial agents.Keywords: Erm gene; iMLSB resistance; mecA; methicillin-resistance; MRSA